Edukasi Dampak Penggunaan Gadget Pada Anak Usia Dini: Penelitian - Cheriani; Muh. Fahrul; Irwan Pradana; Nurul Syafika; Umi Agustiana; Riska Damayanti; A. Imel Wiguna; Ayu Safitra8; Nelli Rezkina Shandra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The use of gadgets among elementary school children has significantly increased, bringing both positive and negative impacts. While gadgets can serve as effective learning tools through educational applications and digital literacy, excessive use may lead to problems such as reduced social interaction, decreased learning concentration, and eye health risks. This study aims to provide education to students of SD Inpres 6/75 Libureng regarding the impacts of gadget use and to foster awareness of its wise utilization. The research employed an educational approach through counseling, interactive discussions, and Q&A sessions with 40 fifth- and sixth-grade students as research subjects. The findings revealed that prior to the educational program, most students primarily used gadgets for entertainment, such as playing games (45%) and watching videos (35%), while learning-related use was relatively low (15%). After the educational intervention, a significant improvement was observed in students’ understanding: the high-level understanding category increased from 15% to 45%, while the low category decreased from 50% to 15%. These results demonstrate that educational approaches are effective in enhancing children’s digital literacy from an early age. Thus, this study contributes to raising awareness of the importance of parental supervision and teacher guidance to ensure that gadget use supports children’s learning and overall development.